Jilbab sebagai Representasi Simbolik Mahasiswi Muslim di Universitas Indonesia - Ramadhini, Eveline (Masyarakat: Jurnal Sosiologi, 2017)
Jilbab or veil is a special cloth in Islam religion, particularly for women. The users are increased significantly in a recent decade in Indonesia. Not to mention also the issue about using of veil in higher education is important in which the discourse about religion is getting easier for being spread by Islamic activists. This article attempts to explain that the phenomenon of differentiation about variation of using veil that occur in campuses is because the differentiation of legitimation from the variation group in Islam itself; Tarbiyah, Hizbut Tahrir Indonesia (HTI), and Salafi. The main argument from this article is that jilbab or veil being used because the context of teology or a form of commitment to the religion which being manifestated in each of the groups. Jilbab is eventually not only being used because of the commitment in teology, but also because of the conformity that is done by a person, so that she can be accepted socially by each variation groups that has been mentioned. Research method that being used is qualitative research which tries to depicts the variation of using jilbab or veil in higher education as it becomes symbol from the variation in Islam (HTI, Salafi, andTarbiyah) which also conduct collective identity. The implication is that there is social boundaries from one group to other groups which suffered contestation, yet there is no serious conflict between them as the individuals inside those groups are already being educated.